Anatomic variants of the subscapular-thoracodorsal arterial system: A radiologic analysis of 200 arterial systems. (February 2022) - Barrett, Thomas F; Orlowski, Hilary; Rich, Jason; Jackson, Ryan S; Pipkorn, Patrik; Puram, Sidharth V
Highlights: CTA Chest effectively mapped vasculature of thoracodorsal-subscapular system. One in five patients lacked a subscapular artery unilaterally or bilaterally. CTA Chest may guide planning for patients with complex reconstructive needs. Abstract: Background: Composite flaps based on the subscapular arterial system are excellent choices for complex defects, including those of the head and neck, though rates of anatomic variants are not well described. Objective: Characterize subscapular-thoracodorsal arterial system in a large cohort of patients using CT chest angiography. Methods: CTA chest studies from 100 adult patients were analyzed to characterize the bilateral subscapular-thoracodorsal arterial systems. Results: Out of 200 arterial systems, 25 (12.5%) were lacking a subscapular artery, with the thoracodoral and circumflex scapular arteries arising independently off of the axillary (or other nearby vessels). Strikingly, the subscapular artery was absent bilaterally in 5 patients and absent unilaterally in 15 patients, meaning that one in five patients harbored abnormal anatomy on at least one side. There was no radiographic evidence of atherosclerosis in the studied vessels in any patient, including smokers and patients with atherosclerosis in other vessels. Conclusion: Variations in the subscapular-thoracodorsal arterial system appear more frequent than previously described. For select patients requiring complex reconstruction using the scapular system, CTA chest may aide surgical planning.